Aderência e satisfação às intervenções e mudanças neuropsicológicas em pessoas idosas: ensaio clínico randomizado - Pereira, Graziele Norberto (Universidade Federal de São Carlos, 2024)
Purpose:To assess the impacts of adherence and satisfaction with interventions on changes in neuropsychological risk factors for falls in older adults with a history of falls. Methods: This controlled, randomized, single-center clinical trial was conducted with Brazilian community-dwelling older adults with a history of at least 2 falls in the past 12 months. Participants were divided into two groups: the Intervention Group (IG) and the Control Group (CG), with assessments at baseline and after 16 weeks. The IG participated in a case management program, including a multidimensional assessment, explanation of fall risk factors, an individualized intervention plan, and monitoring. The CG received monthly health-related guidance. Evaluations included clinical and sociodemographic data, neuropsychological measures (cognition, depressive and anxiety symptoms, fear of falling), adherence to intervention and satisfaction with interventions. Results: The study recruited 523 individuals, of whom 62 were randomized. In the end, 55 participants completed the study, with 26 in the control group (CG) and 29 in the intervention group (IG). Over the 16-week period, 7 participants dropped out, and the average adherence rate was 80.27%. The intervention showed higher satisfaction in the IG compared to the CG (p=0.046), but there was no significant impact on fall risk factors between the groups. No adverse effects were reported. Conclusion: It is concluded that adherence and satisfaction did not significantly influence changes in fall risk factors.
Adherence and satisfaction to neuropsychological interventions and changes in older people: a randomized clinical trial
Keywords: Acidentes por quedas; Gestão de riscos; Pessoas idosas; Saúde; CIENCIAS DA SAUDE::SAUDE COLETIVA